Environmental Factors Influencing Adoption of Canadian Guidelines on Smoking Cessation in Dental Healthcare Settings in Quebec: A Qualitative Study of Dentists' Perspectives - Pascaline Kengne Talla; Marie-Pierre Gagnon; Aimée Dawson (MDPI AG, 2016)
Background: This study aimed to understand dentists' perspective of the environmental determinants which positively or negatively influence the implementation of Canadian smoking cessation clinical practice guidelines (5As: Ask-Advise-Assess-Assist-Arrange) in private dental clinics in Quebec. Methods: This study used a qualitative design and an integrative conceptual framework composed of three theoretical perspectives. Data collection was conducted in individual semi-directed interviews with 20 private dentists lasting between 35 and 45 min. The audio-recorded data were transcribed verbatim, followed by a directed content analysis. Results: Some of the barriers identified to counselling in smoking cessation were lack of time, patient attitude, lack of prescription of nicotine replacement therapies, lack of reimbursement, and the lack of training of the dental team. Enablers cited by participants were the style of dentist's leadership, the availability of community, human and material resources, the perception of counselling as a professional duty, and the culture of dental medicine. In addition to these variables, dentists' attitude and behaviour were affected by different organisations giving initial or continual training to dentists, governmental policies, and the compatibility of Canadian smoking cessation guidelines with the practice of dentistry. Conclusion: Our findings will inform the development of smoking cessation interventions in dental healthcare settings.